The NeuroPhilosophy of Physics: A Grand Unification of How Brain and Mind Shape Our Perception of the Universe - Barzilai, Roy (Journal of NeuroPhilosophy, 2023)
The advancement of modern science, particularly in neuroscience and physics, may have reached the level of knowledge that enables us to be at the cusp of a new grand unified theory of the nature of our mind and how it shapes our perception of reality and evolution of science itself. This grand leap forward requires a paradigm shift towards greater integration of different scientific disciplines under the emerging new field of complex, dynamic systems, such as our brain and the universe, describing how the complex organization of matter is driven by energy flows. This new paradigm enables us to build a new scientific framework by exploring theories in philosophy, physics, biology and neuroscience; weaving them together into a holistic view of the human mind and the nature of physical reality, as in complex systems the whole is greater than the sum of its parts. Throughout the history of philosophy the fundamental question of how the mind perceives reality has shaped its fundamental branches: metaphysics, considering the nature of reality, and epistemology, studying how our mind gains knowledge of reality. This article shall apply new theories in neuroscience, including neuroendocrinology and how it regulates the sociocultural evolution of civilization (Barzilai, 2019; 2023), and cognitive neuroscience, particularly the predictive mind paradigm and free energy principle, to explore the rise of modern science and physics since the Enlightenment, and gain better understanding of both neuroscience and physics.